Ewing Sarcoma/Pnet pre-sacral: case report - Batistão, Guilherme T.; Tiezzi, Giovana F. M.; Salge, Ana Karina M.; Abate, Débora T.R.S.; Olegário, Janainna G. P.; Silva Junior, Edgar L. da; Pereira, Antônio P.; Padulla, Susimary A. T.; Silva, Renata C.Rossi e (Medicina (Ribeirao Preto), 2015)
Ewing’s sarcoma is a type of bone tumor that has aggressive behavior, which mainly affects individuals below 30 years and predominantly in males. The family of tumors includes Ewing a spectrum of neuroectodermal of primitive cells tumors which are embryonic cells migrating from the neural crest. In this report we present a male patient, 19 years, admitted to the emergency room with back pain, weakness of the lower limbs, difficulty urinating and right femur fracture a year ago. Requested magnetic resonance imaging of the pelvis and lumbosacral spine showed a presacral mass lesion and extramedullary and intradural lesions. Patient has been subjected to the pathological examination that showed Ewing’s sarcoma / primitive neuroectodermal tumor. Surgery for spinal decompression and subsequent radiotherapy and chemotherapy have been conducted.